Transformational Leadership on Work Engagement Through Psychological Empowerment as a Mediating Variable - Bani, Ronald Sulle; Tjahjono, Heru Kurnianto (Unit Research and Knowledge, School of Business and Management, Institut Teknologi Bandung, 2025)
Abstract. Digitalization is an important thing for companies today. Many start-ups utilize technology to improve efficiency, flexibility, and connectivity in various aspects of business. The Indonesian Information and Communication Technology Creative Industry Society (MIKTI) said that the development of start-ups that utilize digital technology in Indonesia is very high and experiencing rapid growth (Rahman, 2024). Indonesia ranked sixth globally at the beginning of 2024 in terms of the highest number of start-ups, totaling 2,562, while Jakarta was recognized as the city with the second-best start-up ecosystem at the global Top Emerging Ecosystem level (Startupranking, 2024). The millennial generation is one of the generations that will fill important positions in companies in the future, a generation that is close to technology, they are often called